(untitled) (Jurnal Mekanikal, 2018)
This paper investigates the performance of a split room air conditioner in the special-purpose laboratory room. In order to evaluate the performance, an experimental set-up is constructed. The experimental components consist of a split room air conditioner which has, a hermetic compressor, a condenser, an evaporator, capillary tube and two fans. For on-line reading purposes , it uses data acquisition system and power meter. The unit is installed in the energy conservation laboratory with the room volume of 16.8 m’ at Faculty of Engineering, Universiti Malaya, Kuala Lumpur. Experimental result is obtained for various ambient temperatures. The electricity consumption and coefficient ofperformance ofthe system are measured and presented as a function ofthe ambient temperature.